Super-cute macarons : bake and decorate delicious treats for any occasion - Liu, Loretta (London : Ryland Peters & Small, 2014)
The macaron is a chic and delicious French treat - perfect for many occasions. But you don't have to stop there! In this adorable book, experienced pastry chef Loretta Liu shows you how to take the macaron one step further. First, achieve a batch of perfect light-as-air macarons as your base and then decorate them to create edible art that will delight and amaze your friends and family.
Includes index.
600-699
Keywords: Macarons